Water management systems at Shikha Ecovillage - Panda, Sibaji (Regen-D, 2023)
This book introduces Shikha Ecovillage in the eastern Indian state of Odisha, and describes the components of its water management systems: Water sources; domestic water use; agricultural water use; wastewater and water conservation; and water systems maintenance. The book also functions as a companion book to a Serious Game published by Ishara Press, where the same topic is presented as a playable collection of multimedia materials. The book and game were created by local practitioners at Shikha Ecovillage along with specialists in gamification at Ishara Press. Shikha is built on 10 acres of land and has a tropical climate with seasonal monsoon rains. The residents practice chemical-free horticulture and off-grid living based on solar electricuty and water from the adjacent Mahanadi river. The site includes a boarding school for deaf children and promotes eco-learning. The appendix of the book includes all game materials for printing and self-assembly.